Electromagnetic Noise Characteristic Analysis and Acoustic Optimization of Reactor Acoustic Package - Liangliang LI; Jie DING; Jun CHEN; Xiaobin ZANG; Yulong ZHU; Zhenpeng LI (机车电传动)
In order to solve the common problem of excessive electromagnetic noise in the high frequency electric reactor acoustic package, the subway energy feeder device was selected as the research object, and the vibration and noise tests of it were carried out systematically. Then, the characteristics of acoustic and vibration source and transmission path of the electric reactor were analyzed by combining test and simulation result. Results show that high frequency structural vibration and radiated noise caused by magnetostriction of reactor core is the main sound source of the acoustic package. The louver of reactor pack is the main acoustic transmission path and its sound energy proportion is up to 80.14%. Finally, A targeted sound absorption and insolation optimization scheme was developed based on the sound source characteristics and sound propagation characteristics of the reactor acoustic package,and the overall noise reduction effect was up to 8 dB(A). The research has great reference significance for the analysis of vibration noise characteristics of high frequency reactor and the optimization design of acoustic package of reactor pack.